Penentuan Pemilihan Lokasi Usaha Terbaik Menggunakan Metode AHP dan TOPSIS - Chairina, Bella; Mesra, Trisna; Belen, Maria; Alfian, Wahyu; Simanjuntak, Frans Risky; Pratama, Rizky (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Selecting a business location is a important strategic decision for UMKM, often hindered by subjectivity. This research aims to determine the best business location in Dumai City for UMKM owners. The methodology integrates the Analytic Hierarchy Process (AHP) for criteria weighting and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) for alternative ranking. Data were collected from 20 respondents via questionnaires and interviews. Evaluation criteria included rental cost, accessibility, number of competitors, and location crowdedness . AHP results identified "nearby competitors" as the most significant criterion with a weight of 0.34. TOPSIS analysis selected "Near Offices" as the best alternative with a preference value of 0.63, followed by the city center (0.56), residential areas (0.33), and campus areas (0.29). These findings provide an objective basis for entrepreneurs in location decision-making to minimize investment risks.